Analisis Pengaruh Ukuran Perusahaan Terhadap Laba Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Lubis, Suandi (Journal Research of Economic and Bussiness, 2025)
The purpose of this study is to determine whether firm size has an effect on the profit of manufacturing companies listed on the Indonesian Stock Exchange. This study consists of firm size variables as independent variables and company profit as dependent variables. The data described are the company’s annual financial reports for the period 2019 to 2024 using purposive sampling of 100 companies. From the results of the study, it is known that company size shows a value on the alpha coefficient of 5% (t-stat = 4.441> 1.667) and prob. 0.000 <0.05. Based on the results of the study, the hypothesis accepted is that firm size has a significant effect on the level of profit in manufacturing companies listed on the Indonesian Stock Exchange for the period 2019-2024. Keywords: Firm Size, Profits